2012
DOI: 10.1016/j.jmatprotec.2011.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of sub-100nm IDT SAW devices on insulating, semiconducting and conductive substrates

Abstract: Keywords: E-beam lithography Insulating layers Charge accumulation Anti-static layerThis work describes the electron-beam (e-beam) lithography process developed to manufacture nano interdigital transducers (IDTs) to be used in high frequency (GHz) surface acoustic wave (SAW) applications. The combination of electron-beam (e-beam) lithography and lift-off process is shown to be effective in fabricating well-defined IDT finger patterns with a line width below 100 nm with a good yield. Working with insulating pie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…For the bare glass substrates, an extra step is added: a thin layer of the conducting polymer Espacer 300Z is spin-coated on top of the resist before e-beam lithography in order to avoid charging. 56,57 This conducting layer is removed using deionized water before the development of the resist. All nanostructure dimensions are confirmed using scanning electron microscopy and atomic force microscopy measurements.…”
Section: Samples and Experimental Setupmentioning
confidence: 99%
“…For the bare glass substrates, an extra step is added: a thin layer of the conducting polymer Espacer 300Z is spin-coated on top of the resist before e-beam lithography in order to avoid charging. 56,57 This conducting layer is removed using deionized water before the development of the resist. All nanostructure dimensions are confirmed using scanning electron microscopy and atomic force microscopy measurements.…”
Section: Samples and Experimental Setupmentioning
confidence: 99%
“…deposited by spin-coating before the e-beam lithography step in order to avoid charge effects [30,31]. Then, before the development step, this conductive thin layer is removed by deionized water during 1 min.…”
Section: Fabrication Of Gold Nanostructures On Gold Underlayer and Onmentioning
confidence: 99%
“…Because of the insulating behavior of the Sc 0.26 Al 0.74 N thin film, as well as of the underlying polycrystalline diamond layer, an organic antistatic layer (Espacer 300Z, Showa Denko) was spun on top of the ZEP520 resist to avoid charge accumulation during e‐beam lithography …”
Section: Methodsmentioning
confidence: 99%
“…For this, diamond outstands, since it exhibits the highest acoustic velocity. Several studies have reported SAW devices fabricated on heterostructures with diamond substrates working in the 2–15 GHz frequency range …”
Section: Introductionmentioning
confidence: 99%